Evaluation of Precision and Recall of Five Web OPACs of the Select Universities - Nabi, Somaira; Shafi, S.M. (DESIDOC Journal of Library & Information Technology, 2017)
The paper presents the results of a study about the five Web OPACs of Northern Indian Universities namely, Aligarh Muslim University, University of Delhi, Jawaharlal Nehru University, University of Kashmir, and Punjab University after administering thirty three standard search terms in the field of Economics to the selected Web OPACs for discovering and retrieving information about the knowledge resources held by the respective universities. These Web OPACs were evaluated by taking into account the first twenty results pertaining to each ‘search query’ for estimation of relative recall and precision. The study reveals that ‘Mean Relative Recall’ falls in a low range in relation to precision.